2017
DOI: 10.2174/0929867324666170227115019
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenines and PACAP in Migraine: Medicinal Chemistry and Pathogenetic Aspects

Abstract: L-kynurenine, kynurenic acid, and pituitary adenylate cyclase-activating polypeptide may have fundamental roles in the initiation of migraine headache attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 173 publications
(218 reference statements)
0
9
0
Order By: Relevance
“…The two active forms of PACAP cross the BBB in different ways: PACAP1-27 enters via transmembrane diffusion attributable to its lipophilic property, whereas PACAP1-38 uses a carrier-mediated peptide transport mechanism [127]. The role of PACAP1-38 has been suggested in the ethiopathology of migraine, though some aspects are still yet to be revealed [128][129][130]. PACAP1-38 was detected in the TG [131], in the TNC [132], and also in the parasympathetic otic and sphenopalatine ganglia [133][134].…”
Section: Pituitary Adenylate Cyclase-activating Polypeptide (Pacap)mentioning
confidence: 99%
See 1 more Smart Citation
“…The two active forms of PACAP cross the BBB in different ways: PACAP1-27 enters via transmembrane diffusion attributable to its lipophilic property, whereas PACAP1-38 uses a carrier-mediated peptide transport mechanism [127]. The role of PACAP1-38 has been suggested in the ethiopathology of migraine, though some aspects are still yet to be revealed [128][129][130]. PACAP1-38 was detected in the TG [131], in the TNC [132], and also in the parasympathetic otic and sphenopalatine ganglia [133][134].…”
Section: Pituitary Adenylate Cyclase-activating Polypeptide (Pacap)mentioning
confidence: 99%
“…Tryptophan, one of the essential amino acids, is the precursor of 5-HT and L-kynurenine under physiological conditions. The kynurenine pathway has been previously presented in details [128,144]. Briefly, it is a complex metabolic pathway with a lot of neuroactive products ending with NAD + [145].…”
Section: Kynurenic Acid (Kyna)mentioning
confidence: 99%
“…Based on these observations, early-phase RCTs are currently running to evaluate the efficacy and safety of mAbs targeting PAC1-receptor or PACAP1-38 [158]. Recent preclinical and clinical studies have revealed a new possible aspect of migraine management by influencing the kynurenine pathway [159][160][161][162][163]. Experimental studies with electrically activated trigeminovascular system pointed to a direct link between PACAP and the kynurenine pathway in rats [164].…”
Section: Five-year Viewmentioning
confidence: 99%
“…Elevated levels pf PACAP1-38 were found in the ictal phase compared to the interictal phase in migraine patients [109], and the intravenous administration of PACAP1-38 caused delayed migraine-like headache [110]. Although PACAP1-38 seems to play a crucial role in migraine, some aspects of the nociceptive effects of PACAP1-38 in migraine pathophysiology are still unsettled [111,112]. PACAP1-38 causes mast cell degranulation in the dura mater leading to the activation of peripheral trigeminal nerve fibers [113,114].…”
Section: Pituitary Adenylate Cyclase-activating Peptidementioning
confidence: 99%